Manajemen Tenaga Pendidik SDTQ Al-Mujahidin Surakarta - Lathifa Rosyida; Ratna Dewi Wahyuningsih; Arini Nurul Husna; Fitria Jamilatul Fahmi (IAIN Syekh Nurjati Cirebon, 2023)
Human resource management, especially teachers, is a key element in an educational institution. Teachers play an important role in the educational process. This research aims to determine the form of teachers management through recruitment, induction and orientation programs, placement and classification of teachers, developing and coaching programs, and teachers appraisal at SDTQ Al-Mujahidin. This research uses descriptive qualitative research. Data collection was carried out by observation, interview, and documentation. Analysis was carried out by collecting data, reducing data, presenting data, and verifying data. The results of this study indicate that the form of teachers management at SDTQ Al-Mujahidin is coordinated by the school and the foundation. Recruitment is carried out to find qualified teachers according to the criteria and needs. After recruiting, the school held an orientation program for new teachers so that they have the same perception in teaching to achieve the school's goals. Teachers are placed and classified based on criteria, needs, and the results of teachers appraisal. The school also holds development and training programs so that teachers can develop their skills. In addition, as a form of evaluation for teachers, the school is assisted by the foundation conducting teachers appraisal and evaluations related to teaching, and the result will be used as a reference for updating schools programs in the future.Keywords: Teachers Management, Recruitment, Orientation, Development, Teachers Appraisal.